2019
DOI: 10.1038/s41598-019-48987-4
|View full text |Cite
|
Sign up to set email alerts
|

Milk-derived miRNA profiles elucidate molecular pathways that underlie breast dysfunction in women with common genetic variants in SLC30A2

Abstract: Studies in humans and pre-clinical animal models show milk-derived miRNAs reflect mammary gland function during lactation. The zinc transporter SLC30A2 /ZnT2 plays a critical role in mammary gland function; ZnT2-null mice have profound defects in mammary epithelial cell (MEC) polarity and secretion, resulting in sub-optimal lactation. Non-synonymous genetic variation in SLC30A2 is common in humans, and several common ZnT2 variants are associated with changes in mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
(86 reference statements)
2
13
0
Order By: Relevance
“…Studies have shown that many factors related to mother and baby, such as gestational stage (preterm or term), lactation stage, age, environmental factors, diet, newborn sex, maternal health status, and affect of HM composition 19‐21 . Although some of these factors do not seem possible to affect the microRNA profile of HM, there are very few studies on this subject 22,23 . Our best knowledge is that the study we conducted was the first to investigate the effect of delivery method (cesarean or normal delivery) on the miRNA profile of colostrum.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that many factors related to mother and baby, such as gestational stage (preterm or term), lactation stage, age, environmental factors, diet, newborn sex, maternal health status, and affect of HM composition 19‐21 . Although some of these factors do not seem possible to affect the microRNA profile of HM, there are very few studies on this subject 22,23 . Our best knowledge is that the study we conducted was the first to investigate the effect of delivery method (cesarean or normal delivery) on the miRNA profile of colostrum.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, future studies will need to address if milk-derived exosomal miRNAs can be transferred from bovine milk to humans and regulate gene expression in humans. Alternatively, such exosomes may act directly on cells such as MECs (mammary epithelial cells): Kelleher et al could recently show that miRNAs are involved in MEC signaling and intriguingly, also appear to be required for healthy breast functions ( Kelleher et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Less invasive samples, such as saliva or sputum are often preferred over blood or sera. Indeed, miRNAs have been found in almost all biofluids, including saliva (Min et al, 2018), urine (Ben-Dov et al, 2014, breast milk (Kelleher et al, 2019), and tears (Kim et al, 2019), however, the use of these less invasive sample types would depend on the underlying disease. For example, salivary miRNAs may be useful for the diagnosis of mouth infections (Min et al, 2018) but may not be useful for infections in other areas of the body.…”
Section: Validation and Translation Of Mirna Diagnosticsmentioning
confidence: 99%